Symptomatology of the temporomandibular dysfunction related to parafunctional habits in children - Juliana P. Tosato; Daniela Ap. Biasotto-Gonzalez (Universidade Estadual de Campinas, 2015)
The study focused on verifying the prevalence of Temporomandibular Dysfunction in children, correlating it to their parafunctional habits. A questionnaire was utilized, which was answered by the mothers of 90 children aging three to seven years old (49 girls and 41 boys). The questionnaire inquired whether the child presented pain in the TMJ, head, ears, or in the neck region; tiredness or difficulty when chewing; if he/she used pacifier; habits like biting pens, chewing gum, teeth grinding or clenching, and biting the nails. Among the interviewed girls, 53% showed some sign or symptom of TMD, while among the boys, this prevalence was 39%. The most common complaint was headache. When considering the habits, they were more frequent among the children who presented pain or discomfort. So, parafunctions can be an important factor contributing to the etiology of the dysfunctions.